Paleodischarge reconstruction using oxbow lake sediments complicated by shifting hydrological connectivity. (10th December 2021) - Shen, Zhixiong; Aeschliman, Molly; Conway, Nicholas
Abstract: Alluvial sedimentary records attract great attention for quantitative paleoflood studies because they may preserve continuous high-resolution archives in lowland floodplains that are most vulnerable to inland flooding. The coarse-grained flood deposit in oxbow lakes emerges as a promising paleoflood proxy due to its sensitivity to flood magnitude and high preservation potential. Previous work has established a coarseness-discharge correlation for the instrumental period that was subsequently used to retrodict paleodischarge of older flood deposits. However, it has not been tested whether this correlation applies to older deposits that may represent different lake hydrological connectivity due to plug-bar growth and river migration. Furthermore, overbank sedimentation is known to be episodic and may not scale with flood magnitude. Here we investigate this issue by comparing peak annual discharge and the coarseness of a two-stage infill sequence of a ~60 yr old oxbow lake in South Carolina, USA. We found that local morphology had the first-order control and was responsible for the sedimentation shift in the lake. There is a strong linear coarseness-discharge correlation in the upper section of the lake infill. However, this correlation overestimated the flood magnitude for flood deposits in the lower section. This finding suggests that oxbow lake sediments can be greatly useful for paleoflood reconstruction, but this may be complicated by shifting hydrological connectivity. Therefore, the stratigraphic context of an oxbow lake needs to be well understood to derive paleodischarge from the sediments properly. Highlights: Local morphology has the first-order control on flood deposits in oxbow lakes. Flood magnitude controls lake-sediment coarseness during stable morphologic control. Shifting hydrological connectivity may compromise paleodischarge reconstruction.